Onset Laktasi, Inisiasi Menyusui Dini, dan Frekuensi Antenatal Care sebagai Penentu Keberhasilan Pemberian ASI Eksklusif pada Ibu Primipara: The Onset Lactation, Early Initiation Breastfeeding, and Frequency of Antenatal Care as Determinants of Successful Exclusive Breastfeeding in Primipara Mothers - Shofiya, Dian; Sumarmi, Sri; Sulistyono, Agus; Suyanto, Bagong; Rachma, Rizky Aulia; Rosyida, Ade Riezma Amrina (Universitas Airlangga, 2024)
Background: Since 2016 the City of Surabaya has provided assistance and mentoring for pregnant mothers and infants during the first 1000 days of life. This initiative aims have been to alleviate stunting on children and increase exclusive breastfeeding coverage on breastfeeding mothers. However, the target for exclusive breastfeeding coverage has yet been achieved, and the level of coverage remains low despite these efforts. Objectives: The aim of this study was to determine the effect of the onset of lactation, early initiation breastfeeding frequency of antenatal care on exclusive breastfeeding in primipara mothers. Methods: The research design was cross-sectional; the samples were 130 of 378 primipara mothers and lactating pregnant women who were selected by cluster random sampling. The data were analyzed using both Chi-Square and Logistic Regression analysis α=0.05. data was collected in April 2021. Results: The results showed that there was a significant relationship between ANC, EIB, and onset of lactation with EB (x2=3.145; p-value=0.008, x2=18.745; p-value<0.001, and x2=47.147; p-value<0.001). Conclusions: ANC, EIB, and onset of lactation are determining the success of EB.